Introduction - Raji, Babak (A+BE | Architecture and the Built Environment, 2018)
The main aim of this research is to reduce the energy demand of tall office buildings through architectural design. To achieve high levels of energy-saving, however, it is important to acquire a good understanding of how architectural design strategies can influence the total energy use (and different energy end-uses) individually and as a group. Energy simulations, if well-validated, can help us to correctly apply design strategies to achieve considerable energy-savings.